Preparation of Metal Oxide-based Oxygen Carriers Supported with CeO2 and Î³-Al2O3 for Chemical Looping Combustion - Qasim, M. (John Wiley and Sons Inc, 2021)
The development of efficient oxygen carriers (OCs) in chemical looping combustion (CLC) exhibited tremendous achievement considering inherent CO2 capture. The selectivity of CO2 in the CLC process depends on the performance of employed OCs during multiple redox cycles. Different types of OCs were prepared, including 5wtNi/5wtCe/Î³-Al2O3, 5wtLa/5wtCe/Î³-Al2O3, and 5wtPr/5wtCe/Î³-Al2O3, using the wet impregnation method and characterized by scanning electron microscopy/energy-dispersive X-ray spectroscopy, temperature-programmed reduction, and thermogravimetric analysis (TGA). The redox reactivity of OCs was investigated through TGA and tubular furnace reactor. The as-prepared OCs revealed higher thermal stability along with excellent oxygen capacity. Pr/Ce/Î³-Al2O3-based OCs showed moderate oxygen capacity, which may increase by the addition of active metals. Â© 2021 Wiley-VCH GmbH